2007
DOI: 10.1177/102490790701400302
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of an Emergency Department Toxicology Team in the Management of Acute Intoxication

Abstract: To evaluate the impact of the recently established Emergency Department (ED) Toxicology Team of Queen Mary Hospital (QMH) in the management of acute intoxication. Method: A descriptive comparative study with retrospective data collection from all intoxicated and suspected intoxicated patients over two separate half-year periods in 2001 and 2006, before and after the establishment of the ED Toxicology Team in July 2005. Data on reasons of intoxication, drugs and substances involved, ED treatments, patient dispo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 8 publications
0
16
1
Order By: Relevance
“…There was no cost saving calculated. Units overseas have also shown similar reductions in the average LOS …”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…There was no cost saving calculated. Units overseas have also shown similar reductions in the average LOS …”
Section: Introductionmentioning
confidence: 66%
“…Units overseas have also shown similar reductions in the average LOS. 5,6 A dedicated clinical toxicology unit (CTU) was formally established with admission rights to the Princess Alexandra Hospital (PAH) being granted in February 2014 after a transitional period during 2013. The aim of the unit is to coordinate and improve the quality of care of the toxicological patient by providing 24/7 consultation and inpatient management for patients who have been poisoned or envenomed.…”
Section: Introductionmentioning
confidence: 99%
“…All of the articles had length of stay as one of their outcomes. Six of the papers consistently demonstrated a reduction in overall hospital length of stay – some by comparison to data with previous services , some by comparison to a local hospital or regional/national average . However, one article reported no such effect, though the original data for this outcome was not provided .…”
Section: Resultsmentioning
confidence: 96%
“…Four articles reported specifically on this outcome. Two of the articles reported no change in mortality after initiation of inpatient toxicology services , and one article reported no change in patient outcomes and no change in ED re‐attendance or hospital admission . However, one article (that contemporaneously compared between sites and teams) reported that patients managed at a specialist centre by an inpatient toxicology team had a lower mortality than expected, by up to 5.48%, significantly more than other cohorts .…”
Section: Resultsmentioning
confidence: 98%
“…This model of care improves patient outcome and shortens the length of stay for medical treatment. 6,7 Such improvements might explain the observed good outcome for Chan et al's cohort 4 of patients with paracetamol overdose.…”
mentioning
confidence: 95%